Effect of Sun, Oven and Freeze-Drying on Anthocyanins, Phenolic Compounds and Antioxidant Activity of Black Grape (Ekşikara) (Vitis vinifera L.) - Çoklar, H.; Akbulut, M. (South African Journal of Enology and Viticulture, 2017)
The aim of this study was to determine whether a change occurs in the phenolic compounds and antioxidant activity of grapes after drying. Grapes pre-treated with potassium hydroxide solution were dried using three different drying methods, namely freeze drying, oven drying and sun drying. The effectiveness of the drying methods was evaluated in terms of total phenolic content, antioxidant activity (ABTS, FRAP and DPPH), individual phenolics and anthocyanins. Losses in total phenolic content of the grapes were found to be 1.89, 20.26 and 46.79% for freeze-, oven- and sun-dried grapes respectively. The DPPH and ABTS antioxidant activities of the grapes decreased after drying by all three methods, while an increase was observed in the FRAP value of freeze-dried grapes compared to the fresh sample. No significant effect of drying methods was observed on the gallic acid, 2,5-dihydroxybenzoic acid and (-)-epigallocatechin gallate contents of the grapes. The highest levels of procyanidin B1, (+)-catechin, (-)-epicatechin, (-)-epicatechin gallate, chlorogenic acid, trans-resveratrol and rutin were determined in freeze-dried grapes. Sun and oven drying caused drastic decreases in all anthocyanins, while no loss of anthocyanin was observed in freeze-dried grapes. Sun drying was found as the most detrimental drying method for grapes in terms of phenolic compounds and antioxidant activity when compared to the other drying methods.